Getting to the Heart of the Matter: Myocardial Injury, Coagulopathy, and Other Potential Cardiovascular Implications of COVID-19 - Aaron Schmid; Marija Petrovic; Kavya Akella; Anisha Pareddy; Sumathilatha Sakthi Velavan (International Journal of Vascular Medicine)
COVID-19 was primarily identified as a respiratory illness, but reports of patients presenting initially with cardiovascular complaints are rapidly emerging. Many patients also develop cardiovascular complications during and after COVID-19 infection. Underlying cardiovascular disease increases the severity of COVID-19 infection; however, it is unclear if COVID-19 increases the risk of or causes cardiovascular complications in patients without preexisting cardiovascular disease. The review is aimed at informing the primary care physicians of the potential cardiovascular complications, especially in patients without underlying cardiovascular disease. A comprehensive literature review was performed on cardiac and vascular complications of COVID-19. The primary cardiac and vascular complications include myocarditis, acute coronary syndrome, myocardial injury, arrhythmia, heart failure, shock, multisystem inflammatory syndrome, venous and arterial thrombotic events, stroke, and coagulopathy. A detailed analysis of the pathogenesis revealed six possible mechanisms: direct cardiac damage, hypoxia-induced injury, inflammation, a dysfunctional endothelial response, coagulopathy, and the catecholamine stress response. Autopsy reports from studies show cardiomegaly, hypertrophy, ventricular dilation, infarction, and fibrosis. A wide range of cardiac and vascular complications should be considered when treating patients with confirmed or suspected COVID-19 infection. Elevated troponin and natriuretic peptides indicate an early cardiac involvement in COVID-19. Continuous monitoring of coagulation by measuring serum D-dimer can potentially prevent vascular complications. A long-term screening protocol to follow-up the patients in the primary care settings is needed to follow-up with the patients who recovered from COVID cardiovascular complications.